2020
DOI: 10.3389/fphys.2020.565667
|View full text |Cite
|
Sign up to set email alerts
|

Wnt Pathway: An Emerging Player in Vascular and Traumatic Mediated Brain Injuries

Abstract: The Wnt pathway, which comprises the canonical and non-canonical pathways, is an evolutionarily conserved mechanism that regulates crucial biological aspects throughout the development and adulthood. Emergence and patterning of the nervous and vascular systems are intimately coordinated, a process in which Wnt pathway plays particularly important roles. In the brain, Wnt ligands activate a cellspecific surface receptor complex to induce intracellular signaling cascades regulating neurogenesis, synaptogenesis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 264 publications
(545 reference statements)
0
21
0
Order By: Relevance
“…For instance, the Wnt pathway is associated with the regulation of critical biological processes including neurogenesis, synaptogenesis, neuronal plasticity, synaptic plasticity, angiogenesis, vascular stabilization, and inflammation. 42 , 43 This pathway was also reported to be involved in neuroprotection and neurorestoration following TBI, 44–46 and therefore could explain the ability of HPPL to support differentiation of neuronal cells and exert neuroprotective activity. 15 On the other hand, the analysis of cortical proteome changes afforded by HPPL in both TBI models clearly revealed its ability to downregulate many proteins/pathways linked to inflammation, synapses or mitochondria, which are initially upregulated post-injury, and confirmed, at a larger scale, our targeted gene expression analyses and biochemical studies.…”
Section: Discussionmentioning
confidence: 98%
“…For instance, the Wnt pathway is associated with the regulation of critical biological processes including neurogenesis, synaptogenesis, neuronal plasticity, synaptic plasticity, angiogenesis, vascular stabilization, and inflammation. 42 , 43 This pathway was also reported to be involved in neuroprotection and neurorestoration following TBI, 44–46 and therefore could explain the ability of HPPL to support differentiation of neuronal cells and exert neuroprotective activity. 15 On the other hand, the analysis of cortical proteome changes afforded by HPPL in both TBI models clearly revealed its ability to downregulate many proteins/pathways linked to inflammation, synapses or mitochondria, which are initially upregulated post-injury, and confirmed, at a larger scale, our targeted gene expression analyses and biochemical studies.…”
Section: Discussionmentioning
confidence: 98%
“…Wnt signaling plays a crucial role in presynaptic assembly, postsynaptic differentiation at vertebrate peripheral neuromuscular synapses, stem cell differentiation, and the development and maintenance of the CNS [63][64][65]. Recent evidence suggests that it also regulates vascular stability, BBB integrity, and inflammation [66]. In the canonical Wnt pathway or Wnt/β-catenin pathway, Wnt ligands bind to receptors of the Frizzled (FZD) and low-density lipoprotein-related protein (LRP) families on the cell surface and activate several cytoplasmic relay components, including GSK-3β and adenomatous polyposis coli (APC), finally signaling to β-catenin.…”
Section: Neuroprotective Molecular Signaling Of Hupa Against Admentioning
confidence: 99%
“…When the extracellular ligand binds to the cell surface receptor, the intracellular segment of the surface receptor was activated, which transmits extracellular signals into the cells. Previous studies have shown that the Wnt signaling pathway is activated in some cardiovascular and cerebrovascular diseases, and plays an important role in the proliferation, migration, apoptosis, and differentiation of vascular smooth muscle cells, which is one of the mechanisms of MMD [30][31][32][33]. Therefore, the role of the Wnt signaling pathway in MMD is worthy of further investigation.…”
Section: Discussionmentioning
confidence: 99%